DINAMIKA POLITIK PEMBENTUKAN RANCANGAN PERATURAN DAERAH (RANPERDA) RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH (RPJMD) PERUBAHAN DI KOTA PEKANBARU TAHUN 2020 - Raqib, Tengku Mulyadi; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Regional Medium Term Development Plan (RPJMD) is one of the development planning documents that must be prepared by the local government 6 months after the regional head is appointed. The vision and mission in the Regional Medium Term Development Plan (RPJMD) is the vision and the mission of the elected regional head offered to the community during the implementation of the campaign in the implementation of the Regional Head Election (PILKADA) and made adjustments that refer to the existing Regional Long Term Development Plan (RPJPD). This means that the Regional Medium Term Development Plan (RPJMD) is a political contract between the regional head and the citizens during his 5 year term.The purpose of this research is to find out the Political Dynamics that occurred in the Establishment of The Draft Regional Regulation (Ranperda) Regional Medium Term Development Plan (RPJMD) Changes in the Pekanbaru City in 2020. This research uses method qualitative approach with research type is descriptive. In data collection the author uses interview and dokumetasi techniques.The results of this study showed that there are dynamics or pro and contra to Ranperda about the Amendment to Perda No. 17 of 2017 on RPJMD Pekanbaru City Year 2017-2022 which in the draft Ranperda is not included in the current condition of the Covid-19 Pandemic that causes some to disagree when discussed by Pansus, resulting in the unfulfillment of the quorum of the plenary meeting of the Pansus Report on May 11, 2020, resulting in the meeting being postponed and re-held on May 12, 2020. But it has not yet been fulfilled, but a mutual agreement is still being made. During the evaluation process in Riau Provincial Government, the Riau Provincial Government decided to return the draft Ranperda to be included in the current condition. And finally a new joint agreement was reached on September 30, 2020 and next established into local regulations or perda. Keywords: Political Dynamics, Changes in RPJMD, Development Planning